To Indonesian  PROBLEMATIKA PEMBELAJARAN TARKIB AL JUMLAH DALAM PEMBELAJARAN BAHASA ARAB PADA SISWA KELAS VIII DI MTs NEGERI 2 PRINGSEWUI 2 PRINGSEWU: ID - amrulloh khoirul ma'arif; Syeh Al Ngarifin; Hamid, Abdul (Jurnal Pendidikan Bahasa Arab L-DHAD, 2022)
People who study Arabic, especially in structure of Arabic language material, will experience problems which are reflected in the form of errors in usage, both in the process of creating or composing sentences and in the process of translating sentences. From the results of observations that the author made regarding the learning of tarkib al sum in eight class MTs Negeri 2 Pringsewu, it is clear that the Arabic language teacher there has played a good role in learning Arabic, especially in the material of structur, however students' understanding is still low. This research aims to find out what problems there are in learning structure of Arabic language for students and how to overcome these problems. In this research, the author used a qualitative approach with a qualitative descriptive method. In collecting data the author used several methods, observation, interviews, and documentation. The results of the research are a lack of knowledge about the basic material of structure of Arabic language so that students will experience difficulties in the next material, a lack of student motivation in learning the structure of Arabic language material, low student interest in reading Arabic books and other supporting books, teachers in delivering the material Lessons are less varied and have not been maximized in using learning media, the delivery of the structure of Arabic language material is not sequential, and only focuses on the material contained in the textbook, there is a lack of examples of the structure of Arabic language material being delivered. The efforts made to overcome this problem are motivating students to be more enthusiastic in the process of learning Arabic, especially in the tarkib material, always repeating material that has been studied before adding the next material, sequencing the material that will be presented to students, providing more complex teaching in Tarkib material through Tarkib learning strategies. Be more creative in delivering teaching materials so that it doesn't seem monotonous and doesn't make students bored in the learning process.